Poetry slam: uma experiência com a linguagem poética e seus vínculos com a cultura e a vida - Dantas, Lucimar Américo (2019)
The subject of study of this research was the literary genre ‘poetry’ with a focus on Ensino Fundamental II (the four last years of elementary school), considering that among the literary genres, this one is the most marginalized in primary education. In general, the literary reading is shortly valued in the formation process of the proficient reader in Brazilian schools. We also contemplate on this research the Poetry Slam (‘battles’ of spoken poetry) as part of the intervention proposal that was applied on a 9th grade classroom from Ensino Fundamental II in order to contribute with promoting literature literacy with the poetry genre. The Poetry Slam is considered a form of marginal literature that, according to some researchers on the subject “periphery”, needs to be legitimized. The methodology used in this study was the research-action on which the participation of people involved (researcher and students) on the problems investigated is of paramount importance. The marginalization of poetry on the classroom was investigated on this study as an attempt to outline probable causes for the lack of interest of the student in this literary genre, as well as possible practices of literary literacy that could contribute with the literary literacy with the genre, always seeking to relate it to the students culture and lives. On the whole, the poetry contributes with the integral formation of the student: his personality, his intellectual and affective development, his comprehension of reality and of himself.